A New Paradigm in Torque Transfer: Rethinking Shaft Key Placement - Matus Veres; Frantisek Brumercik; Ronald Bastovansky; Robert Kohar (Machines)
In this study, an innovative approach to torque transmission mechanisms within the context of hub–shaft connections is introduced by exploring the viability of a transverse key configuration. Unlike traditional longitudinal key placements, the proposed method positions the key perpendicularly to the rotational axis, resembling a pin joint at the interface of the shaft and the hub. This research primarily aims to elucidate the maximum torque capacity of such a connection, juxtaposed against conventional methodologies. Employing a rigorous analytical framework, equations originally designed for pin connections are adapted to suit the unique geometric and loading conditions presented by the transverse key. This adaptation is essential in quantifying the resultant torque that the connection could sustain without failure. The study meticulously accounts for the variations in key dimensions and the inherent limitations posed by the method’s reliance on the end-face connection strategy. Comparative analyses underscore the manufacturing advantages of the proposed method, notably its reduced machinery requirements, by leveraging standard milling processes over more complex machining operations that are traditionally associated with keyway or keyseat creation. However, the findings also highlight the compromised torque transmission capability due to the reduced contact area, a significant consideration for designers. This research contributes to the broader discourse on mechanical connection innovations, offering a novel perspective on torque transmission solutions. It provides a foundation for future exploration into alternative key configurations, potentially revolutionizing hub–shaft connection designs in applications constrained by manufacturing capabilities or cost considerations.